MISCAST: MIssense variant to protein StruCture Analysis web SuiTe. Issue Volume 48:Issue W1(2020) (13th May 2020) - Iqbal, Sumaiya; Hoksza, David; Pérez-Palma, Eduardo; May, Patrick; Jespersen, Jakob B; Ahmed, Shehab S; Rifat, Zaara T; Heyne, Henrike O; Rahman, M Sohel; Cottrell, Jeffrey R; Wagner, Florence F; Daly, Mark J; et al.
Abstract: Human genome sequencing efforts have greatly expanded, and a plethora of missense variants identified both in patients and in the general population is now publicly accessible. Interpretation of the molecular-level effect of missense variants, however, remains challenging and requires a particular investigation of amino acid substitutions in the context of protein structure and function. Answers to questions like 'Is a variant perturbing a site involved in key macromolecular interactions and/or cellular signaling?', or 'Is a variant changing an amino acid located at the protein core or part of a cluster of known pathogenic mutations in 3D?' are crucial. Motivated by these needs, we developed MISCAST (missense variant to protein structure analysis web suite; http://miscast.broadinstitute.org/ ). MISCAST is an interactive and user-friendly web server to visualize and analyze missense variants in protein sequence and structure space. Additionally, a comprehensive set of protein structural and functional features have been aggregated in MISCAST from multiple databases, and displayed on structures alongside the variants to provide users with the biological context of the variant location in an integrated platform. We further made the annotated data and protein structures readily downloadable from MISCAST to foster advanced offline analysis of missense variants by a wide biological community.